2009
DOI: 10.1002/jbt.20279
|View full text |Cite
|
Sign up to set email alerts
|

Protection of half sulfur mustard gas–induced lung injury in guinea pigs by antioxidant liposomes

Abstract: The purpose of this study was to develop antioxidant liposomes as an antidote for mustard gas-induced lung injury in a guinea pig model. Five liposomes (LIP-1, LIP-2, LIP-3, LIP-4, and LIP-5) were tested with differing levels of phospholipid, cholesterol, phosphatidic acid, tocopherol (alpha, gamma, delta), N-acetylcysteine (NAC), and glutathione (GSH). A single dose (200 microL) of liposome was administered intratracheally 5 min or 1 h after exposure to 2-chloroethyl ethyl sulfide (CEES). The animals were sac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
56
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 38 publications
(58 citation statements)
references
References 33 publications
2
56
0
Order By: Relevance
“…This protection was associated with inhibition of CEES-induced activation of TNF-␣, NF-B, and reactive oxygen species . A similar protection against CEES-induced lung injury with antioxidant liposomes containing NAC and tocopherols (␣, ␥, ␦) was demonstrated in our laboratory recently (McClintock et al, 2006;Mukherjee et al, 2009).…”
Section: Introductionsupporting
confidence: 61%
See 4 more Smart Citations
“…This protection was associated with inhibition of CEES-induced activation of TNF-␣, NF-B, and reactive oxygen species . A similar protection against CEES-induced lung injury with antioxidant liposomes containing NAC and tocopherols (␣, ␥, ␦) was demonstrated in our laboratory recently (McClintock et al, 2006;Mukherjee et al, 2009).…”
Section: Introductionsupporting
confidence: 61%
“…This notion was further evident by the attenuative effects of antioxidant liposome containing NAC and tocopherols on CEES-induced lung injury Mukherjee et al, 2009). Our previous study also reported that CEES exposure not only initiate a series of signaling events but also causes oxidative stress Das et al, 2003).…”
Section: Discussionmentioning
confidence: 93%
See 3 more Smart Citations